Pembentukan Masyarakat Berakhlak Mengikut Politik Islam - Mohamad, Shukeri (Jurnal Usuluddin, 1998)
This article tries to explain how the Islamic Politic construct an ethical society. It’s also tries to prove that the Islamic Politic which based on the revelation can implement this message.